The Roles of Kisspeptin System in the Reproductive Physiology of Fish With Special Reference to Chub Mackerel Studies as Main Axis - Ohga, Hirofumi; Selvaraj, Sethu; Matsuyama, Michiya (Frontiers in Endocrinology, 2018)
Kisspeptin, a novel neuropeptide product of the Kiss1 gene, activates the G protein-coupled membrane receptor GPR54 (now termed Kiss1r). Over the last 15 years, the importance of the kisspeptin system has been the subject of much debate in the mammalian research field. At the heart of the debate is whether kisspeptin is an absolute upstream regulator of gonadotropin-releasing hormone secretion, as it has been proposed to be the master molecule in reproductive events and plays a special role not only during puberty but also in adulthood. The teleostean kisspeptin system was first documented in 2004. Although there have been a number of kisspeptin studies in various fish species, the role of kisspeptin in reproduction remains a subject of controversy and has not been widely recognized. There is an extensive literature on the physiological and endocrinological bases of gametogenesis in fish, largely derived from studying small, model fish species, and reports on non-model species are limited. The reason for this discrepancy is the technical difficulty inherent in developing rigorous experimental systems in many farmed fish species. We have already established methods for the full life-cycle breeding of a commercially important marine fish, the chub mackerel, and are interested in understanding the reproductive function of kisspeptins from various perspectives. Based on a series of experiments clarifying the role of the brain–pituitary–gonadal axis in modulating reproduction in chub mackerel, we theorize that the kisspeptin system plays an important role in the reproduction of this scombroid species. In this review article, we provide an overview of kisspeptin studies in chub mackerel, which substantially aids in elucidating the role of kisspeptins in fish reproduction.